A new species of Cochemiea (Cactaceae, Cacteae) from Sinaloa, Mexico - García Morales, Leccinum Jesús; González González, Rodrigo Homero; García Jiménez, Jesús; Iamonico, Duilio (Instituto de Ecología, A.C., 2020)
Background and Aims: Cochemiea is a genus which currently comprises five species occurring in Mexico. It is morphologically characterized by cylindrical decumbent to prostrate stems and by a long red-scarlet zygomorphic perianth, presumably specialized for hummingbird pollination. As part of the ongoing taxonomic studies on the North Mexican flora, a population discovered by Thomas Linzen in 2012 in central Sinaloa (Mexico), previously identified as Mammillaria sp., actually refers to a Cochemiea species and cannot be ascribed to any of the known species of that genus. As a consequence, we here propose to describe this population as a a new species for science. Methods: The work is based on field surveys (autumn 2018 and spring 2019) in central Sinaloa, examination of herbarium specimens, and analysis of relevant literature. Its conservation status was assessed following the guidelines of the IUCN; AOO and EOO were calculated with the program GeoCAT. Key results: Cochemiea thomasii is described and illustrated from Sinaloa. The new species is morphologically similar to C. halei from which it differs by the hanging stems, the larger conical tubercles, less numerous and shorter central spines, and the ovoid fruits. A diagnostic key of the known Cochemiea species is included. Conclusions: Cochemiea thomasii is endemic to the state of Sinaloa where it occupies a small area. On the basis of the criteria B2a (geographic range) and C (small population) of IUCN, the new species can be assessed as Critically Endangered (CR) or Vulnerable (VU). Adopting the precautionary approach, Cochemiea thomasii is considered as Critically Endangered (CR).